The importance of combining open-ended and closed-ended questions when conducting patient satisfaction surveys in hospitals - Keren Semyonov-Tal; Noah Lewin-Epstein (Elsevier, 2021)
Background: Using data obtained from the National Satisfaction Survey in General Hospitals, 2014, the present study examines patients' satisfaction with medical care and hospitalization conditions in the public hospitals in Israel. Using the framework of 'voice' expression the study examines the added-value of analyzing verbal responses to gage patient satisfaction. Methods: The analysis utilizes a series of closed-ended questions to construct indexes of patients' satisfaction with medical doctors, nursing staff, and hospitalization conditions for a sample of 11,098 patients who were hospitalized in the 25 public hospitals. In addition, a content analysis was applied to the verbal responses (open ended question) to create categories of complaints. Using logistic regression models, we analyzed the social and demographic correlates of high satisfaction, and estimated the relationship between verbal complaints and satisfaction scores. Results: Analysis of the satisfaction measures shows very high levels of patient satisfaction coupled with low variance. Yet, detailed analysis of responses to an open-ended question reveals considerably more critical assessments of the hospitalization experience. Conclusion: The findings illustrate the limitations of closed-ended satisfaction items as the sole instrument for assessing the quality of medical care and underscore the value of the use of mixed methods as a more nuanced approach.